Pembangunan Olaharga Ditinjau dari Sport Devepment Index : Aspek Partisipasi dan Kebugaran Jasmani Masyarakat di Kabupaten Rembang (Indonesian Journal for Physical Education and Sport, 2021)
One of the districts of Central Java is Rembang Regency. This regency has not yet known the level of sports development as seen from the sport development index in the aspects of sports participation and physical fitness. The method used in this research is descriptive quantitative then analyzed using the sport development index. The research location in Rembang Regency was taken a sample of 3 districts, namely Sarang, Kragan and Pancur. The sample was determined by stratified random sampling and cluster sampling, the sample amounted to 90 people and was divided into 3 districts with categories of 30 people per district. One sub-district consists of 10 children, 10 adolescents, and 10 adults, with the provisions per age category of 5 boys and 5 girls. The data collection instruments were carried out by means of observation, interviews, documentation, questionnaires and tests. The results of this research are the level of community participation in sports in Kragan District 0.56, Sarang District 0.59, Pancur District 0.52. Meanwhile, the physical fitness level of the people in Kragan District was 0.54, Sarang District was 0.62 and Pancur District was 0.57. The conclusion of this study, the participation level and physical fitness of Rembang Regency which were taken from 3 districts were included in the medium category. Even though it is in good condition, the Rembang Regency government must also add many facilities for physical fitness to be more productive.